2021
DOI: 10.2147/ijgm.s296814
|View full text |Cite
|
Sign up to set email alerts
|

Association of Age and Sex with Metabolic Syndrome in Taiwanese Adults

Abstract: Objective This study aimed to investigate the association of age and sex with metabolic syndrome (MS) in Taiwanese adults. Methods We extracted information of 4307 men and 4783 women aged 30–70 from the Taiwan Biobank. Results The interaction between age and sex on MS was significant (p-value = 0.0001). After stratification by sex, men and women aged 50–70 years (reference: 30≤age<50 years) had a higher risk of MS. The odds ratio (OR), 95% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…The results of this study showed that age, residence, occupation, history of hyperlipidemia, history of hyperuricemia, hip circumference, HbA1c, BMI, and RHR were related to MetS. A study in Taiwan Province, China addressed that residents aged 50-70 had a higher risk of MetS than residents aged 30-50 [17]. As we all know, MetS is closely related to obesity, hyperglycemia, hypertension.…”
Section: Discussionmentioning
confidence: 76%
“…The results of this study showed that age, residence, occupation, history of hyperlipidemia, history of hyperuricemia, hip circumference, HbA1c, BMI, and RHR were related to MetS. A study in Taiwan Province, China addressed that residents aged 50-70 had a higher risk of MetS than residents aged 30-50 [17]. As we all know, MetS is closely related to obesity, hyperglycemia, hypertension.…”
Section: Discussionmentioning
confidence: 76%
“…While a positive relationship between age and MetS has been reported [28,29], the relationship between sex and MetS has been inconsistent. Several studies revealed conflicting results of the sex differences in prevalence of MetS from disparate populations [5,[30][31][32][33]. Whether the sex differences exist with certain distribution in metabolic/obesity phenotypes is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia was defined as uric acid > 7.2 mg/dL in men, >6.5 mg/dL in women, or that under urate-lowering therapy. MtS was defined by the meeting of at least 3 of the following 5 criteria proposed by the Health Promotion Administration, Ministry of Health and Welfare of Taiwan: (1) fasting blood glucose ≥ 100 mg/dL or previously diagnosed DM; (2) systolic blood pressure ≥130 mmHg or diastolic blood pressure ≥85 mmHg or a previous diagnosis of HTN; (3) high-density lipoprotein cholesterol < 40 mg/dL in men or <50 mg/dL in women; (4) triglyceride ≥ 150 mg/dL; and (5) waist circumference ≥ 90 cm in men or ≥80 cm in women [ 31 ].…”
Section: Methodsmentioning
confidence: 99%